Effectiveness of digital media technologies in South African football events marketing - Williams, Thato (My University, 2016)
The research report set out understand the effectiveness of the digital marketing platforms or channels, such as Facebook, Twitter, YouTube, etc. as communication channels for the professional football teams in South Africa. The research is set against the backdrop of the lack of football match attendance for the majority of the Premier Soccer League (PSL) matches beside the Kaizer Chiefs and Orlando Pirates derbies. The PSL, as well as the soccer teams, needs to attract more fans to the stadia in order to attract more sponsors and increase their revenue in terms of the gate taking and television rights. This study applied qualitative methodology in the collection of research data to inform this study. This method has been used in a number of marketing studies and has been proven to be most reliable when collecting marketing data and the results are more accurate than other methods. The study’s main focus was aimed at understanding the professional football teams’ adoption of digital media and social media in their marketing activities and the results thereof indicated that only a handful of these teams, mainly the successful teams such as Kaizer Chiefs, Orlando Pirates and Mamelodi Sundowns, had to some extent developed communication strategies to support their digital media campaigns but they still lack executive support. The digital media platform is growing rapidly globally and this platform has been successfully adopted in other football leagues around the world and could be used in response to the attendance crisis in the PSL.
Keywords: Soccer -- South Africa -- Marketing. Internet marketing -- South Africa. Social media -- South Africa -- Marketing.